Adrenocorticotropic Hormone-Independent Cushing Syndrome with Bilateral Cortisol-Secreting Adenomas - Ku, Eu Jeong (Korean Endocrine Society, 2013)
A 48-year-old woman was incidentally found to have bilateral adrenal masses, 2.8 cm in diameter on the right, and 2.3 cm and 1.7 cm in diameter on the left, by abdominal computed tomography. The patient had a medical history of hypertension, which was not being controlled by carvedilol, at a dose of 25 mg daily. She presented with signs and symptoms that suggested Cushing Syndrome. We diagnosed adrenocorticotropic hormone (ACTH)-independent Cushing Syndrome based on the results of basal and dynamic hormone tests. Adrenal vein sampling (AVS) was performed to localize a functioning adrenal cortical mass. AVS results were consistent with hypersecretion of cortisol from both adrenal glands, with a cortisol lateralization ratio of 1.1. Upon bilateral laparoscopic adrenalectomy, bilateral ACTH-independent adrenal adenomas were found. The patient's signs and symptoms of Cushing Syndrome improved after surgery just as the blood pressure was normalized. After surgery, the patient was started on glucocorticoid and mineralocorticoid replacement therapy.